(untitled) (Książnica Śląska, 2025)
The author of the text describes, analyzes and evaluates general German bibliographies about Silesia, published in Germany from the turn of the 19th century until the end of World War II. The subject of the analysis are the content and formal features of the bibliography, its scope and coverage: territorial, chronological, linguistic, formal/ publishing and written. The principles of selecting bibliographic material, the internal composition of the bibliography and information apparatus were examined. All considerations are located in a historical perspective, showing the origins and development of Silesian territorial bibliographies.